Spatial and temporal variability of pollutants in the bottom sediments in the northwest part of the Black sea - Berlinskyi, Nikolai; Safranov, Tamerlan (Publishing House of Lviv Polytechnic National University, 2016)
The level of pollution of the bottom sediments in the Northwest shelf of the Black Sea is examined. Modern data are compared with those of the late 20th century and their variability over 30 years. Substantial increase (by two orders) of copper, lead and nickel concentration has been marked.
Keywords: Black Sea; Northwest shelf; pollutant; bottom sediments